THE EFFECT OF SHOPEE LIVE FEATURES AND INFORMATION QUALITY ON ONLINE IMPULSIVE BUYING OF FASHION PRODUCTS (CASE STUDY ON STUDENTS AS E-COMMERCE CUSTOMERS SHOPEE AT THE FACULTY OF ECONOMICS AND BUSINESS) - Syahrul Hidayat; Khairina AR; Jullimursyida; Halida Bahri (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to analyze the influence of Shopee Live Features and Information Quality on Online Impulse Buying on Fashion Products, with a case study ofShopee Shopee Ecommercecustomer students at the Faculty of Economics and Business, Universitas Malikussaleh. This study used a quantitative method with purposive sampling, involving 108 respondents. Data were collected through questionnaires and analyzed using descriptive analysis, multiple linear regression, and validity and reliability tests. The results show that the Shopee Live Feature and Information Quality significantly affect Online Impulse Buying of Fashion Product, with the Shopee Live Feature having the greatest influence. An Adjusted R Square of 0.473 indicates that 47.3% of the Online Impulsive Buying variation is explained by an independent variable and 52.7 is influenced by other variables that were not studied in this study.